2011
DOI: 10.3384/ecp11057186
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Enzymatic Hydrolysis of A Marine Macro-Alga by Dilute Acid Hydrolysis Pretreatment

Abstract: Abstract:The marine macro-alga Nizimuddinia zanardini was harvested from Persian Gulf to assess its biomass for fermentable sugar production. Hydrolysis of the macro-alga was investigated in two stages to evaluate the conversion of cellulose and hemicelluloses in biomass to corresponding monomeric sugars. The biomass was first subjected to dilute sulfuric acid pretreatments at 121 °C and then to enzymatic saccharification (45°C, pH 4.8) at different retention times. The results showed the ability of the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
(6 reference statements)
1
15
0
Order By: Relevance
“…This has often been investigated with different combinations of reaction times, temperatures and pressures as these parameters have shown to influence the maximum final yields of sugar that are liberated from the seaweed biomass [12,15,16]. Studies have also proved that a two stage process (an initial acid chemical pre-treatment followed by subsequent enzyme hydrolysis; similar to that commonly conducted for lignocellulosic biofuels) can increase the yields of fermentable sugars by at least double [17,18]. For example, Ra et al [19] added a blend of enzymes (Viscozyme-L and Celluclast; Novozymes, Denmark) for the hydrolysis of a pre-treated slurry of red algal species G. verrucosa, liberating 84.2% of the theoretical maximum of the species' total carbohydrate content [19].…”
Section: Introductionmentioning
confidence: 99%
“…This has often been investigated with different combinations of reaction times, temperatures and pressures as these parameters have shown to influence the maximum final yields of sugar that are liberated from the seaweed biomass [12,15,16]. Studies have also proved that a two stage process (an initial acid chemical pre-treatment followed by subsequent enzyme hydrolysis; similar to that commonly conducted for lignocellulosic biofuels) can increase the yields of fermentable sugars by at least double [17,18]. For example, Ra et al [19] added a blend of enzymes (Viscozyme-L and Celluclast; Novozymes, Denmark) for the hydrolysis of a pre-treated slurry of red algal species G. verrucosa, liberating 84.2% of the theoretical maximum of the species' total carbohydrate content [19].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of the pretreatment temperature, time and hydrolysis condition of several macroalgae pretreatments process are provided in Table 4 (Lee et al, 2013;Borines et al, 2013;Yazdani et al, 2011). The results indicated that glucose yield from M. pyrifera after IHRHW pretreatment was much higher than that obtained after conventional pretreatments.…”
Section: Application Feasibility Of Ihrhw Pretreatmentmentioning
confidence: 89%
“…Glucan and xylan concentrations were calculated according to Eqs. (1) and (2), where the factors of 0.9 and 0.88 reflect the weight loss as a result of glucose-to-glucan and xylose-to-xylan conversion, respectively (Yazdani et al, 2011).…”
Section: Analysis Of Solid Samplesmentioning
confidence: 99%
See 2 more Smart Citations